Dilemma of Identification Patients Palliative Care Needs in Critical Care Unit - Astuti, Nining Puji; Sriyono, Sriyono; Yunitasari, Esti; Kurniawati, Ninuk Dian; Baidhowy, Arief Shofyan (Indonesian Journal of Global Health Research, 2024)
Palliative care is start from diagnosis of serious illness until death and bereavement care. But, the term “Palliative Care” often mistakenly regarded identical to “End of Life Care” without any treatments. It’s caused dilemma among nurses to give maximum care of palliative care needs or let the patients get minimum of care. Methods: The aim of this article is to evaluate the dilemma palliative care needs in Intensive Care Unit. This is a case study report used a qualitative approach of 3 palliative patients in ICU used descriptive case study as well as in depth-interviews with patient’s family, nurses and internist. Results and Discussion: We present a case report of 3 patient who had been admitted to hospital with cancer and need palliative care in ICU. Patients subsequently suffered a pulmonary metastase with multiple organ failure. However the goal of end of life care for dying patients is to prevent or relieve suffering as much as possible while respecting the patient’s desires. But it is still a dilemma in Indonesia, especially palliative patients in ICU. According to medical decision, patients in ICU should receive maximum treatment, but if patient is facing multiple organ failure nurse should consider to providing palliative care. Conclusions: Palliative care approaches and provision within intensive care units can significantly impact care outcomes and increase the quality-of life people with end-of life period. Palliative care not to reduce the dose of drugs and patient care.